EFEKTIVITAS PEMBERIAN AROMA TERAPI LAVENDERDAN MASSAGE EFFLEURAGE TERHADAP PENURUNAN NYERI MENSTRUASI PADA REMAJA PUTRI DI SMAN 10 PEKANBARU - Yesi Septina wati; Yoanda Dwi Ardini (JOMIS (Journal of Midwifery Science), 2021)
Lavender aromatherapy and effleurage massage are non-pharmacological methods, aromatherapy can reduce pain, stress, anxiety and massage can cause a relaxing effect. The aim was to see the effectiveness of lavender aromatherapy and effleurage massage in reducing menstrual pain in young women. The research design used a pre-experimental and a two-group design as a sample, a pre-test-posttest study of girls who experienced menstrual pain and met the criteria. The data in this study used an observation sheet, the analysis used a paired sample t-test. The results showed that the significance value of 0.000 <0.05, there was a difference between the pre-test and post-test giving lavender aromatherapy and effleurage massage with differences in the lavender aromatherapy group. The high average value of effleurage massage with a difference of 0.16 indicates that young women who experience menstrual pain can apply non-pharmacological treatments to reduce pain due to menstrual pain, one of which is lavender aromatherapy and effleurage massage to reduce the use of pharmacological drugs.